Easily prepared one dimensional zinc oxide crystals, characterization and application in UV photodetector. (2021) - Sarkar, Sudipta Kumar; Gupta, Dipti
Abstract: One dimensional (1D) zinc oxide crystals (ZCs) were prepared using a simple wet chemical route. Structural and morphological characterizations were performed through x-ray diffraction, scanning electron microscopy and transmission electron microscopy. Thus, the prepared sample confirmed the hexagonal crystal phase of zinc oxide and displayed a uniform morphology with 1D structure. The average length and diameter of the prepared ZnO based 1D structure were found to be 8 µm and 0.7 µm respectively. Energy dispersive x-ray spectroscopy and Fourier transform infrared spectroscopy were performed to study the chemical purity of the sample. The prepared sample also showed its excellent ability in ultra-violet (UV) absorption with a sharp absorption peak at 369 nm and a photoluminescence (PL) property with a sharp emission peak at 384 nm. Finally, a UV photodetector device was fabricated with the prepared sample and its photoconductivity with a significant change in resistance was observed upon UV exposure.